2015
DOI: 10.1096/fasebj.29.1_supplement.608.6
|View full text |Cite
|
Sign up to set email alerts
|

A 6‐month chronic toxicity study on green tea polyphenols in middle‐aged ovariectomized rats

Abstract: The project is to evaluate chronic toxicity and safety in middle‐aged ovariectomized rats supplemented with different dosages of green tea polyphenols (GTP) in drinking water. 182 SD were sham (n=39) or ovariectomized (OVX, n=143). Both sham and OVX‐control animals receiving no GTP were assigned for sample collection at baseline, 3, and 6 months. The remaining OVX animals were randomized into 0.15%, 0.5%, 1%, and 1.5% (wt/vol) GTP for 3 and 6 months. Routinely clinical observation was performed. Ophthalmologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…73 The preliminary results showed no mortality or abnormal treatment-related effects, although OVX rats supplemented with GTP at 1.5% dosage had the smallest body weights. 71 In general, GTP intake up to 1.5% dosage for 6 months did not affect hematology, clinical chemistry, or urine analysis. It was observed that bone mass and strength significantly improved with GTP concentration in the drinking water.…”
Section: First Author Year Study Design Treatment Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…73 The preliminary results showed no mortality or abnormal treatment-related effects, although OVX rats supplemented with GTP at 1.5% dosage had the smallest body weights. 71 In general, GTP intake up to 1.5% dosage for 6 months did not affect hematology, clinical chemistry, or urine analysis. It was observed that bone mass and strength significantly improved with GTP concentration in the drinking water.…”
Section: First Author Year Study Design Treatment Resultsmentioning
confidence: 83%
“…It was observed that bone mass and strength significantly improved with GTP concentration in the drinking water. 71 Based on the bone histomorphometric analysis, GTP suppressed both bone formation and bone resorption at cancellous bone of tibia as well as periosteal and endocortical bone of tibia in a dose-dependent manner. 72 The study demonstrated osteoprotective benefits of GTP in OVX-treated animals only at high dosages (1% and 1.5%), and not at lower dosages.…”
Section: First Author Year Study Design Treatment Resultsmentioning
confidence: 99%
See 3 more Smart Citations